Administrative Ecology and Monarchical Governance in Brunei Darussalam and Saudi Arabia: A Comparative Public Administration Analysis - Salsabila Nuur Rahim; Abdul Syauqi Iman (Universitas Muhammadiyah Jakarta, 2024)
This article examines the comparative public administration of Brunei Darussalam and Saudi Arabia, two Islamic monarchies that share important institutional similarities while demonstrating distinctive administrative trajectories. Although both countries are characterised by centralised monarchical authority, Islamic legitimacy, and resource-supported state capacity, their administrative systems differ in scale, historical formation, legal-institutional configuration, and reform orientation. Using a qualitative descriptive method based on documentary analysis and comparative literature review, this study analyses four major dimensions: the form of state, the form of government, the governmental system, and the political system. The article is conceptually informed by comparative public administration and Fred W. Riggs’ administrative ecology, which emphasises the interaction between administrative institutions and their socio-cultural, political, economic, and historical environments. The findings show that Brunei Darussalam institutionalises governance through the philosophy of Malay Islamic Monarchy, which integrates Malay identity, Islamic values, and sultanate authority. Saudi Arabia, meanwhile, derives its administrative legitimacy from the Basic Law of Governance, Sharia, dynastic rule, and consultative mechanisms involving the Council of Ministers, the Shura Council, and religious authority. The study concludes that both countries represent centralised Islamic-monarchical administrative systems, yet Brunei tends to display a smaller-scale paternalistic administrative model, while Saudi Arabia demonstrates a larger, reform-oriented, strategically modernising monarchical administration under Vision 2030.